2017
DOI: 10.4204/eptcs.256.12
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Linear Temporal Logic Tableau

Abstract: For many applications, we are unable to take full advantage of the potential massive parallelisation offered by supercomputers or cloud computing because it is too hard to work out how to divide up the computation task between processors in such a way to minimise the need for communication. However, a recently developed branch-independent tableaux for the common LTL temporal logic should intuitively be easy to parallelise as each branch can be developed independently. Here we describe a simple technique for pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recently, a tree-shaped tableau for LTL has been proposed by Reynolds [22], which only requires a single pass to decide whether a given branch has to be accepted or not. The smaller size of the tree with regards to the full graph structure of previous methods, and its simple rule-based tree search mechanism, led to an efficient implementation [3], a simple and fruitful parallelization [21], and modular extensions to more expressive logics [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a tree-shaped tableau for LTL has been proposed by Reynolds [22], which only requires a single pass to decide whether a given branch has to be accepted or not. The smaller size of the tree with regards to the full graph structure of previous methods, and its simple rule-based tree search mechanism, led to an efficient implementation [3], a simple and fruitful parallelization [21], and modular extensions to more expressive logics [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Various ways of overcoming such a limitation have been proposed in the literature, including incremental [7] and single pass techniques [12]. Recently, a one-pass and tree-shaped tableau system for LTL has been devised [11], which does not build any huge preliminary structure and, thanks to its pure rule-based tree-search structure, proved to be amenable to efficient implementation and easy parallelisation [3,10]. Recent work also suggested that its modular structure makes it possible to easily extend it to other linear time logics (the extension to LTL with past operators is described in [6]).…”
Section: Introductionmentioning
confidence: 99%